Histological changes in the human prostate after radiotherapy and salvage high intensity focused ultrasound - Chalasani, Venu; Martinez, Carlos H.; Williams, Andrew K.; Kwan, Kevin; Chin, Joseph L. (Canadian Urological Association Journal, 2013)
The histological changes (both macroscopic and microscopic) in the prostate following the combination of external beam radiotherapy and salvage high intensity focused ultrasound (HIFU) have not been previously described. This article describes the case of a 65-year-old male who presented with recurrent localized prostate cancer after undergoing external beam radiotherapy for low-risk prostate cancer. He was treated with salvage HIFU, and 4 weeks later presented with symptoms and signs consistent with a prostatorectal fistula. During a period of conservative management, his serum prostate-specific antigen levels started rising after having reached a nadir. A radical cystoprostatectomy and repair of fistula were performed after conservative management failed. Histological changes of dense fibrosis were noted in the region where the prostate should have been located. A literature review of the histological findings in the prostate after HIFU is discussed in this article, as well as the available evidence for the management of patients with local failure after the combination of external beam radiotherapy and salvage HIFU.